Determinants of current account deficits in developing countries - Calderon, Cesar (Policy research working papers / World Bank, 2000)
In developing countries, increases in current account deficits tend to be associated with a rise in domestic output growth and shocks that increase the terms of trade and cause the real exchange rate to appreciate. Higher savings rates, higher growth rates in industrial economies and higher international interest rates tend to have the opposite effect.